Responsiveness and minimally important change for the Manchester-Oxford foot questionnaire (MOXFQ) compared with AOFAS and SF-36 assessments following surgery for hallux valgus. - Dawson, J; Doll, H; Coffey, J; Jenkinson, C (2007)
OBJECTIVES: To assess responsiveness and minimally important change (MIC) for the Manchester-Oxford foot questionnaire (MOXFQ) using anchor and distribution-based approaches. Responsiveness and estimates of minimal clinically important difference (MCID) and minimal detectable change are compared with those from the Short-Form 36 (SF-36) and American Orthopaedic Foot and Ankle Society (AOFAS) measures. METHODS: A prospective observational study of 91 consecutive patients (125 foot operations) undergoing hallux valgus surgery at an orthopaedic hospital. Pre- and 12 month post-surgery, patients completed the MOXFQ and SF-36, and foot surgeons assessed all four AOFAS scores corresponding to four regions of the foot. Transition items were asked about perceived changes compared with before surgery. RESULTS: Mean changes in all domains of each instrument were statistically significant, but foot-specific MOXFQ and AOFAS domains produced much larger effect sizes (>1) than any SF-36 domains, indicating superior responsiveness. Clear associations occurred between transition items and all MOXFQ and AOFAS scores, but with only one (physical function) SF-36 domain. Anchor and distribution-based approaches identified generally comparable measures of MIC, which for the MOXFQ and AOFAS domains were between 1 and 2 standard error of measurement. In metric terms, the MCIDs were 16, 12, and 24 for the MOXFQ Walking/standing, Pain, and Social Interaction domains, respectively. CONCLUSIONS: For hallux valgus surgery, the MOXFQ is highly responsive. Performance is comparable to the AOFAS and notably better than the generic SF-36. Study estimates of MIC for the MOXFQ are useful to inform sample-size calculations for future clinical trials.